Impacts of land use change on ecosystem health in the Chahannur Lake Basin of Inner Mongolia, China - Zheng, Ying; Zhang, Zixuan; Lu, Shuaizhi; Dong, Lei; Guo, Jianying (Frontiers in Ecology and Evolution, 2025)
The Chahannur Lake Basin is a crucial component of the ecological security barrier construction in northern China. Land use changes induced by high-intensity human activities have increasingly triggered a series of ecological and environmental issues, severely threatening the ecosystem health (EH) of the basin. Understanding the impact of land use changes on ecosystem health is of great significance for ecological conservation and territorial spatial planning. This study took the Chahannur Lake Basin as study area, analyzed the spatio-temporal evolution of land use over the past 30 years, systematically evaluated the EH level based on the vitality-organization-resilience-services (VORS) framework, and further revealed the impacts of land use structure and conversions between land use types on EH. The results indicated that (1) the most prominent land use changes were characterized by the continuous expansion of forest and construction land, as well as the sustained contraction in farmland area from 1990 to 2022. (2) The ecosystem of the basin was generally at a moderate healthy level, with a trend of first deteriorating and then gradually improving. The EH demonstrated the strongest positive response to the conversion of farmland to grassland, while grassland degradation and rapid urbanization were unfavorable for the maintenance of high-level EH. (3) Grassland and farmland were identified as the key land use types influencing EH, both exhibiting significant threshold effects. The proportion of grassland area exerted a positive promoting effect, with a threshold of 37.99%, beyond which the promoting effect would be progressively weakened. Farmland, by contrast, exhibited dual effect on EH, with its effect shifting from positive to negative beyond a critical threshold. Strengthening grassland ecosystem protection and restoration, appropriately promoting grassland area expansion, and restricting excessive farmland development are the core strategies to improve EH of the basin. These findings can provide scientific reference for ecological protection and restoration, land use optimization management, and sustainable development in ecologically fragile basin.